Spatial repellency, antifeedant activity and toxicity of three medium chain fatty acids and their methyl esters of coconut fatty acid against stable flies. Issue 1 (29th August 2019) - Roh, Gwang H; Zhou, Xiaaojie; Wang, Yansu; Cermak, Steven C; Kenar, James A; Lehmann, Alexander; Han, Baoyu; Taylor, David B; Zeng, Xiaopeng; Park, Chung Gyoo; Brewer, Gary J; Zhu, Junwei J
Abstract: BACKGROUND: Stable flies are one of the most detrimental arthropod pests to livestock. With changing climates and agronomic practices, they expand their roles as pests and disease vectors as well. Their painful bites reduce livestock productivity, annoy companion animals, and interfere with human recreational activities. Current management technologies are unable to effectively control stable flies. The present study reports new results concerning the contact, spatial repellency, and toxicity of a bio‐based product, coconut fatty acid and their methyl ester derivatives of free fatty acids of C8:0, C10:0 and C12:0 to stable flies. RESULTS: Three medium chain fatty acid methyl esters (C8:0, C10:0 and C12:0 ) showed strong antifeedant activity against stable flies and their strengths were dose‐dependent. Only the C8:0 acid, C8:0 ‐ and C10:0 methyl esters elicited significant antennal responses. Laboratory single cage olfactometer bioassays revealed that coconut fatty acid and C8:0 methyl ester displayed active spatial repellency. All three methyl esters showed strong toxicity against stable flies. CONCLUSION: Antifeedant activity is the main method through which coconut fatty acid deters stable fly blood‐feeding. The C8:0, C10:0 and C12:0 methyl esters act not only as strong antifeedants, but also possess strong toxicity against stable fly adults. Limited spatial repellency was observed from coconut fatty acid and C8:0 methyl ester. © 2019 Society of Chemical Industry Abstract : Three medium chain fatty acid methyl esters derived from coconut fatty acid were demonstrated with a strong feeding deterrence against stable flies. They also displayed significant toxic activity to stable fly.